ANACANTHORUS SP. E NOTOTHECIUM DELEASTOIDEUM (MONOGENEA: DACTYLOGYRIDAE) PARASITANDO SERRASALMUS MACULATUS KNER, 1858 (CHARACIFORMES; SERRASALMIDAE) COLETADO NO RIO DO PEIXE, ESTADO DE SÃO PAULO, BRASIL. - Caramello, Luhan Eduardo; Vieira, Diego Henrique Mirandola Dias; Kozlowiski, Vanessa Doro Abdallah; Silva, Reinaldo José da; Azevedo, Rodney Kozlowiski de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2011)
.